THE CHEMICAL COMPOSITION OF PROCYON - Yushchenko, A. V.; Gopka, V. F. (Одеські астрономічні публікації, 2017)
The review of last studies on the chemical composition of Procyon showed that the abundances of 55 elements were investigated in the atmosphere of Procyon. The abundances of majority of elements are near Solar systems values. The exceptions are Li, Be, B, Se, Te. The possible explanation of tellurium overabundance is proposed.